Outcomes Of Endoscopic Sinus Surgery Versus Medical Therapy In Chronic Rhinosinusitis Patients - Ahmad, siyyar; Ullah, aziz; Ali, Farman; Hafeez, Muhammad; shinwari, wajih ud din; Ahmad, Suhail (Journal of Neonatal Surgery, 2025)
Background: Chronic rhino sinusitis (CRS) impairs quality of life and productivity. When guideline-directed medical therapy (MT) fails, endoscopic sinus surgery (ESS) is considered. Comparative evidence quantifying symptom relief, endoscopic/radiologic improvement, and complication profiles in real-world cohorts remains variable. This study compares outcomes of ESS versus continued MT in adults with CRS. Objectives: To compare patient-reported, endoscopic, and radiologic outcomes between ESS and MT in CRS, and to identify predictors of clinically meaningful improvement. Study Design: A Prospective study. Place and Duration of Study: Department of ENT Pak International Medical College Peshawar, from January 2024 to December 2024. Methods: This Prospective study parallel-group cohort at a tertiary otolaryngology center. Adults with CRS meeting guideline criteria after maximal MT were allocated to ESS or continued MT based on shared decision-making. Outcomes: SNOT-22 change (primary), Lund-Kennedy endoscopic score, Lund-Mackay CT score, olfaction, and adverse events. Assessments at baseline and 3/6/12 months. Analysis used multivariable linear/logistic regression and propensity weighting. Results: A total of N=patients (ESS n= MT n=) were analyzed (mean age ± years; % female). At 12 months, ESS showed greater SNOT-22 improvement than MT (mean Δ vs. adjusted mean difference [95% CI to], p =). ESS also improved endoscopic scores (Δ vs. p =) and olfaction (Δp). Radiologic scores improved primarily in ESS. Complication rates were low and comparable. Predictors of response included baseline SNOT-22 and presence of nasal polyps. Conclusion: In adults with refractory CRS, ESS was associated with larger and clinically meaningful improvements in symptoms and objective measures compared with continued MT, with low complication rates. Baseline disease burden and polyp status modified treatment effect. Findings support ESS for appropriately selected patients after failure of guideline-based MT.